2007
DOI: 10.1007/s11259-007-9013-y
|View full text |Cite
|
Sign up to set email alerts
|

The T963C mutation of TP53 gene does not participate in the clonal origin of canine TVT

Abstract: In dogs, the canine transmissible venereal tumor (CTVT) is the only neoplasm which is not produced by neoplastic transformation of normal cells; the tumor is transmitted from the affected dog to healthy dogs by implantation of one or various clones of cancer cells. Thus, the CTVT of dogs analyzed in various countries reveals similar genetic characteristics and consequently CTVT is considered to have a clonal origin. The CTVTs obtained from dogs in Korea showed the T963C mutation on TP53 gene; this mutation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The utilization of aCGH in the present study therefore allows the first global demonstration of deletion of tumor suppressor genes and over-representation of proto-oncogenes in CTVT. Sequence mutations of the TP53 tumor suppressor gene have been implicated in the origin of CTVT, though their significance is yet to be fully understood (Vazquez-Mota et al 2008). The region of the canine genome encoding TP53 (CFA 5q21) was present in normal copy number in all five cases studied by aCGH, with only a minor underrepresentation in CTVT 72M.…”
Section: Discussionmentioning
confidence: 98%
“…The utilization of aCGH in the present study therefore allows the first global demonstration of deletion of tumor suppressor genes and over-representation of proto-oncogenes in CTVT. Sequence mutations of the TP53 tumor suppressor gene have been implicated in the origin of CTVT, though their significance is yet to be fully understood (Vazquez-Mota et al 2008). The region of the canine genome encoding TP53 (CFA 5q21) was present in normal copy number in all five cases studied by aCGH, with only a minor underrepresentation in CTVT 72M.…”
Section: Discussionmentioning
confidence: 98%
“…Choi and Kim identified a point mutation of the tumour suppressor protein p53 (T963C) resulting in the change of amino acid (Phe–Ser) in TVT cases. Vázquez‐Mota et al concluded that this mutation did not participate in the clonal origin of the tumour, but was acquired at a later stage. Further, TVT tissue from bitches lacks surface oestrogen receptor‐α expression …”
Section: Diagnosismentioning
confidence: 99%
“…This genomic rearrangement has been identified in a large set of globally distributed CTVT tumors, but not in any other canine tissue, and is now considered diagnostic evidence for CTVT (Katzir et al, 1987;Amariglio et al, 1991;Choi et al, 1999;Chu et al, 2001b;Choi and Kim, 2002;Liao et al, 2003b;Murgia et al, 2006;Park et al, 2006;Vazquez-Mota et al, 2008;Rebbeck et al, 2009). It is possible that this rearrangement was present in the germ line of the CTVT founder, that it occurred somatically during the development of the founding CTVT tumor or that it occurred somatically in a CTVT clone that has subsequently achieved global distribution.…”
Section: Ctvtmentioning
confidence: 99%